The Effectiveness of Wordwall Media in Enhancing Arabic Vocabulary Learning Among Fifth-Grade Students at MI Nurussalam Mantingan Ngawi - Sa'idah, Mandrasi Amira; Nabila, Khansa; Yasin, Agus (Universitas Ahmad Dahlan, 2024)
The acquisition of Arabic language skills—listening, speaking, reading, and writing—depends heavily on vocabulary mastery. At MI Nurussalam Mantingan Ngawi, a lecture-centered teaching approach has resulted in low vocabulary proficiency among students. To address this issue, this study investigates the effectiveness of Wordwall media in enhancing vocabulary learning outcomes for 5th-grade students. A quantitative experimental method employing a true experimental design with a post-test-only control group was utilized. Data were collected through tests and documentation, and analysis involved t-tests with homogeneity and normality tests. The findings reveal that Wordwall media significantly improves vocabulary learning outcomes, as indicated by a t-count of 2.994, exceeding the critical values at both the 5% (2.021) and 1% (2.704) significance levels. Consequently, the null hypothesis (Ho) is rejected. This study concludes that Wordwall media is an effective instructional tool for improving Arabic vocabulary mastery and recommends its integration into Arabic language teaching practices.